Students’ perception of a reduction in teaching weeks in a medical programme in Fiji - Rachael Tufui Masilomani; Sophaganie Jepsen; Maria Lourdes Villaruel; Aying Wang; Alena Kotoiwasawasa; Lusiana Naikawakawavesi; Norman Bartolome; Claudia Paterson; Andrew Hill; Maria Concepcion Bartolome (The Asia Pacific Scholar)
Introduction: The MBBS programme at Fiji National University reduced its teaching weeks from 18 to 14 weeks in 2018. The purpose of this study was to assess student perceptions of learning and teachers following the reduction in the number of teaching weeks from 18 to 14 weeks. Methods: A questionnaire was created using a modified Dundee Ready Education Environment Measure (mDREEM) tool (23 items). This was comprised of two subscales; Students Perception of Learning (SPL – 12 items) and Students Perception of Teachers (SPT – 11 items). This was circulated to Year 5 MBBS students through an online survey in 2020. Results: The response rate was 96%. The students regarded their educational environment as positive in both length of teaching weeks, with an overall mDREEM mean score of 63.29 in 18 weeks and 62.03 in 14 weeks. No statistically significant differences were found between 18 week and 14 week scores across mDREEM scores, SPL scores or SPT scores. The highest scoring item over both was ‘teachers are knowledgeable’. Conclusion: A positive perception was noted for both lengths of teaching weeks. Reducing the teaching weeks from 18 to 14 did not statistically significantly reduce students’ perception of their educational environment. Items identified with low scores will give a window of opportunity for lecturers and to improve these areas. Future studies may explore the use of the five subscales of the DREEM tool and this study can be integrated into further evaluations of educational environment at Fiji National University.